Rehabilitation of former Snowy Scheme sites in Kosciuszko National Park. (23rd September 2013) - MacPhee, Elizabeth; Wilks, Gabriel
<x xml:space="preserve">Abstract</x> Ten years of restoration work at 200 sites within Kosciuszko National Park – sites damaged during the construction of Australia's most iconic hydroelectric scheme – is showing substantial progress and is contributing to the protection of the park's internationally significant ecosystems.